2023
DOI: 10.3390/ijms24098451
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Probiotic Bifidobacterium longum in a Lithium–Pilocarpine Model of Temporal Lobe Epilepsy in Rats

Olga E. Zubareva,
Alexandra V. Dyomina,
Anna A. Kovalenko
et al.

Abstract: Epilepsy is a challenging brain disorder that is often difficult to treat with conventional therapies. The gut microbiota has been shown to play an important role in the development of neuropsychiatric disorders, including epilepsy. In this study, the effects of Bifidobacterium longum, a probiotic, on inflammation, neuronal degeneration, and behavior are evaluated in a lithium–pilocarpine model of temporal lobe epilepsy (TLE) induced in young adult rats. B. longum was administered orally at a dose of 109 CFU/r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 126 publications
0
4
0
1
Order By: Relevance
“…Focusing on the advanced stages of epilepsy, particular differences were consistently reported in epileptic rats that showed a significantly diminished freezing time in contextual and tone fear conditioning in comparison to controls at 2 months after pilocarpine ( 52 ) or shortly after 2 months ( 53 ). Similarly, Zubareva et al ( 54 ) showed a contextual memory decline (decreased freezing time in the familiar cage compared to the controls) in pilocarpine rats 60–70 and 70–90 days after SE ( 55 ). Interestingly, Qiu et al ( 56 ) found that pilocarpine rats had most severely impaired fear declarative memory at 2 months after SE, but then improved at 4 months while still performing worse than controls in CFC cues.…”
Section: Contextual Memorymentioning
confidence: 83%
“…Focusing on the advanced stages of epilepsy, particular differences were consistently reported in epileptic rats that showed a significantly diminished freezing time in contextual and tone fear conditioning in comparison to controls at 2 months after pilocarpine ( 52 ) or shortly after 2 months ( 53 ). Similarly, Zubareva et al ( 54 ) showed a contextual memory decline (decreased freezing time in the familiar cage compared to the controls) in pilocarpine rats 60–70 and 70–90 days after SE ( 55 ). Interestingly, Qiu et al ( 56 ) found that pilocarpine rats had most severely impaired fear declarative memory at 2 months after SE, but then improved at 4 months while still performing worse than controls in CFC cues.…”
Section: Contextual Memorymentioning
confidence: 83%
“…We previously demonstrated that epileptogenesis in the lithium-pilocarpine model of temporal lobe epilepsy results in motor activity disorders, altered levels of anxiety, communicative behavior changes, and memory impairments in experimental rats [31]. Therefore, this study aimed to investigate whether the therapy utilized-particularly combination therapy with anakinra and lamotrigine-could prevent TLE rats from developing behavioral disorders.…”
Section: Behavioral Disturbances May Be Improved With Anakinra Lamotr...mentioning
confidence: 99%
“…Recently, it has been found in deeper intestinal microscopic mechanisms that the GM metabolites mediate the bax gene to lower neuronal apoptosis via the cGAS/STING axis in epilepsy [18]. Numerous clinical and preclinical investigations have also demonstrated the potential of probiotics [19][20][21] and fecal microbiota transplantation [22] in ameliorating the GM dysbiosis and mitigating seizures through the augmentation of beneficial microbial populations. Briefly, these data all confirm that the GM may be engaged in the pathophysiological process of the occurrence and development of epilepsy.…”
Section: Introductionmentioning
confidence: 99%